Synthesis of a daptomycin thiolactone analogue via the MeDbz‐linker‐based cyclative‐cleavage approach. Issue 4 (5th January 2022) - Cheung, Carina Hey Pui; Chow, Hoi Yee; Li, Can; Blasco, Pilar; Chen, Kaichao; Chen, Sheng; Li, Xuechen
Abstract: Herein, we report the synthesis of a daptomycin thiolactone analogue via the MeDbz‐linker based on resin self‐cleaving macrocyclization pathway. A detailed investigation of the reaction conditions is reported, including the variation of the cyclization buffer, temperature, concentration, and reaction time. Severe hydrolysis was observed under most of the conditions screened, presumably due to the low reactivity of (2 R, 3 R )‐β‐methylcysteine (thioThr) used. Eventually, pyridine/acetic acid buffer was identified as the most viable solvent system to afford the hydrolysis‐free product. We perceive that this optimized protocol will enable the synthesis of other challenging thiolactone peptides, possibly those involving thioThr or penicillamine. Abstract :